(untitled) (Nexo Revista Científica, 2023)
This study includes tested nine reinforced concrete beams. It’s designed to fail in flexural under two-point load. All beams are classified according to the type of concrete and the percentage of PVA into three groups. The first group including four reinforced geopolymer concrete beams with percent of PVA was 0.2 %; second group including four reinforced geopolymer concrete beams with percent of PVA was 0.75 % and third group including one reinforced normal concrete beam. The results showed when comparing the geopolymer concrete beam with the normal concrete beam, noticed that the ultimate strength is equivalent to many times the normal concrete. The best percentage for improving the ultimate load for beam NO.6 (GSSB10) where the percentage of increase was 132% this beam is reinforced by steel bars 2ɸ12mm at top and 2ɸ16mm at bottom. As for the other beams, the percentage increase in ultimate load was for beam NO.1 (46%), beam NO.2 (99%), beam NO.3 (13%), beam NO.4 (60%), beam NO.5 (58%), beam NO.7 (32%) and beam NO.8 (66%). The maximum deflection in all samples was high compared with the normal concrete, where the ultimate deflection reached 30 mm, while in the normal concrete it was 9.65 mm.